THE CORRELATION BETWEEN STUDENTS’ INTERPERSONAL AND INTRAPERSONAL INTELLIGENCES AND THEIR ENGLISH ACHIEVEMENT AT SMAN 2 KENDARI - Ibrahim, Iin; Sale, Firdaus; Fatmawati, Wa Ode (Journal of Teaching of English, 2020)
The purpose of this study was to investigate the correlation between students’ interpersonal and intrapersonal intelligences and their English achievement. The design of this study was correlation design, and the sample of this study was 90 students which is consists of 140 populations. The sampling was taken by simple random sampling. Moreover, the instruments of this study were interpersonal and intrapersonal intelligences. Based on the result of data computation, it showed that coefficient correlation of students’ interpersonal with (r= -.214).), indicates a low correlation, while students intrapersonal has the high correlation with (r=0.071). The result also shown that the significant value of each students’ interpersonal and intrapersonal intelligences had a significant correlation with their English achievement because its probability value (sig.2 tailed) 0.040 and 0.000 were higher than 0.05. so H1 is definitely accepted and H0 is totally rejected.